Efecto biocida de extractos hidrosolubles de propóleos de abejas Apis mellifera y Trigonas sp sobre Escherichia coli y Staphylococcus aureus - Gil, Marielsa; Monsalve, Catherine; Quintana, Laura; Castrillo, Smirna; Ochoa, Greysys; Perozo, Esther; Briceño, Andris (Vitae, 2022)
El objetivo de esta investigación fue evaluar el efecto biocida del extracto hidrosoluble de propóleos (EHP) de abejas Apis mellifera y Trigonas sp. proveniente de San Cristóbal, Estado Táchira, Venezuela sobre Escherichia coli y Staphylococcus aureus ATCC 25922 y 25923 respectivamente. Se determinó la concentración mínima inhibitoria (CMI) y la concentración mínima bactericida (CMB) utilizando el método de macrodilución en tubos. Se observó que no hubo efecto bacteriostático, pero si bactericida sobre Escherichia coli CMB 50% en el EHP de Apis mellifera, mientras que en Staphylococcus aureus se obtuvo la CMI a 25% y la CMB a 50%. En cuanto al EHP de Trigonas sp. se observó que no hubo efecto bacteriostático para ninguna de las cepas pero se obtuvo una CMB al 100% (puro), tanto para Escherichia coli como para Staphylococcus aureus. Se demostró que los EHP de ambos tipos de abejas tienen efecto antimicrobiano sobre las cepas estudiadas. Title Biocidal effect of water-soluble extracts of propolis from Apis mellifera and Trigona sp bees over Escherichia coli and Staphylococcus aureus Abstract The main focus of this research was to evaluate the biocidal effect of the water-soluble extract of propolis (WEP) from Apis mellifera and Trigona sp bees from San Cristobal, Tachira state, Venezuela, on Escherichia coli and Staphylococcus aureus ATCC 25922 and 25923 respectively. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) was determined using the tubes macrodilution method. It was observed that there was no bacteriostatic effect but a bactericidal one on Escherichia coli MBC 50% on the WEP from Apis mellifera, while it was obtained a MIC of 25% and a MBC of 50% on Staphylococcus aureus. As for the WEP from Trigona sp, it was observed that there was no bacteriostatic effect for any of the strains, but MBC of 100% (pure extract) was obtained for Escherichia coli and for Staphylococcus aureus. It was demonstrated that the WEP from both types of bees have antimicrobial effect on the tested strains